Agroecological transformation in Kenya: partner organizations lead change - Fuchs, Lisa E.; Bolo, Peter; Staiger Rivas, Simone; Korir, Hezekiah; Adoyo, Beatrice; Kuria, Anne; Orero, Levi; Gumo, Pius; Mbelwa, Machio; Sakha, Michael (2024)
In-depth engagement processes and collaboration with the implementing partners of the Agroecology Initiative, Dry Lands Natural Resources Centre (DNRC) and Sustainable Agriculture and Healthy Environmental Program (CSHEP), led these partners to incorporate innovative agroecological co-design processes in their capacity sharing for development activities. This led to 282 participating farmers being exposed to these context-specific operationalization of the agroecology principles. First tangible benefits are an increase in vegetable productivity in systems with low inputs, using sustainable practices and favoring ecological processes.